2007
DOI: 10.3174/ajnr.a0770
|View full text |Cite
|
Sign up to set email alerts
|

Mineralization of the Deep Gray Matter with Age: A Retrospective Review with Susceptibility-Weighted MR Imaging

Abstract: BACKGROUND AND PURPOSE: Susceptibility-weighted imaging (SWI) is an advanced MR imaging sequence that can be implemented at high resolution. This sequence can be performed on conventional MR imaging scanners and is very sensitive to mineralization. The purpose of this study was to establish the course of mineralization in the deep gray matter with age by using SWI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
88
1
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(100 citation statements)
references
References 31 publications
6
88
1
5
Order By: Relevance
“…Mineralization of the putamen includes deposition of iron, calcium, and other metals, all of which could cause local magnetic susceptibility. 7 We attempted to compare sensitivity to local magnetic susceptibility among SWAN, PSI, and T 2 * WI, so diŠerentiat-ing the cause of susceptibility was not our study purpose. Finally, because histological conˆrmation of each lesion was unavailable and impractical, we based diagnosis of cavernous malformation and cerebral microbleed on clinical imagingˆndings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mineralization of the putamen includes deposition of iron, calcium, and other metals, all of which could cause local magnetic susceptibility. 7 We attempted to compare sensitivity to local magnetic susceptibility among SWAN, PSI, and T 2 * WI, so diŠerentiat-ing the cause of susceptibility was not our study purpose. Finally, because histological conˆrmation of each lesion was unavailable and impractical, we based diagnosis of cavernous malformation and cerebral microbleed on clinical imagingˆndings.…”
Section: Discussionmentioning
confidence: 99%
“…1). 7 We used source axial images to compare SWAN, PSI, and 2D T 2 * WI rather than the minimum intensity projections frequently used for SWAN and PSI. Mineralization was graded according to hypointensity that demonstrated the posterolateral to anteromedial gradient of putaminal mineralization with age.…”
Section: Depiction Of Mineralization Of the Putamenmentioning
confidence: 99%
“…All the data processing were operated on a separate workstation (ADW4.3, GE), phase images were high-pass filtered to create corrected phase images with a central matrix size of 64 × 64 (15), in order to remove varying phase shifts which arise predominantly from background field inhomogeneities and air-tissue interfaces (15,27). Twelve structures including bilateral PU, GP, CA, TH, RN, and SN were measured on the corrected phase images, and the phase value ranged from −π to +π.…”
Section: Image Processingmentioning
confidence: 99%
“…To ensure they exist, these hypointensities are confirmed with other pulse sequences such as susceptibility-weighted imaging (SWI) [4], gradient echo (T2*FFE) [5,6], and T2W [7] sequences. In each study, they found that hypointensities increase with age [4], iron storage [8][9][10], calcium deposits from trace metals associated with iron storage [11], and mineralized proximal lenticulostriate arterioles and perivascular spaces [2]. Whatever the cause, using the concentric rectangular blades rotated around the k-space can reduce these hypointense artifacts.…”
Section: Introductionmentioning
confidence: 99%